Meningkatkan Hasil Belajar Pada Materi Tugas Gereja Koinonia Dengan Menggunakan PBL Pada Fase F Di SMK Negeri 9 Surakarta - Uriyani Eka Putri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Welcoming the Golden Indonesia plan map for 2016 to 2045 with a vision of quality education that matches developed countries with the implementation of the Independent Curriculum as one of the efforts of the Ministry of Education and Culture, Research and Technology as a way to perfect the learning system in Indonesia. Implementation of the Independent Curriculum focuses on the use of technology and learning communities to share with each other for teachers, students and academics. One of them is by implementing a learning model that stimulates students to think critically by being actively involved in solving problems adapted to the realities of everyday life. This research was conducted to analyze the use of a learning model that applies critical thinking and solutions in solving problems, namely Problem Based Learning and as a way to improve student learning outcomes. The method in this research uses classroom action research techniques which aim to improve or increase the quality of learning. Through PBL, students are motivated and feel happy in learning Catholic Religious Education and Character, this is because students feel directly involved in the learning process by getting appreciation for the results of their work. The description of this research is very clear that one of the factors for successful learning is the use of learning models in the teaching and learning process.